THE ROLE OF ORGANIZATIONAL COMMITMENT AND PERCEIVED ORGANIZATIONAL SUPPORT IN PROMOTING ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Nadim, Muhammad; Hassan, Muhammad Mubbashar; Abbas, Shakeel; Naveed, Anila (PEOPLE: International Journal of Social Sciences, 2016)
This paper examined the impact organizational commitment and perceived organizational support in promoting organizational citizenship behavior of teacher in private sector universities of Pakistan. The data were collected from 140 teachers working with private sector universities in Pakistan. Multiple methods in the form of regression analysis were used to check the hypothesis. The consequences of the study indicate that organizational citizenship behavior is a factor that fairly depends upon organizational commitment and also on perceived organizational support; furthermore, perceived organizational support and organizational commitment have considerable affirmative impact means it positively influence the organizational citizenship behavior of teaches working in private universities of Pakistan. This study is primarily driven tentatively by the social exchange theory that deliberately lends support to this paper for explaining the idea of perceived organizational support (POS), the norm of reciprocity, and also organizational support theory. This article adds value to the restricted literature regarding the psychological concept that causes the creation of organizational citizenship behavior through the perceptions of organizational support theory concept (Eisenberger et al., 2001; Eisenberger, et al., 1986) and the social exchange theory (Blau, 1964).The paper suggests that if private sector universities in Pakistan desire to cultivate organizational citizenship behavior among its teachers then they must chalk out and implement such strategies that increase employee commitment as well as perceived organizational support (POS).